(untitled) (Global Journal of Management and Business Research, 2020)
In order to control price competition restriction agreements by law, the state needs to accurately identify the price instrument and the influence of the price-use agreement to limit competition. A pricing tool to be used effectively in restraining price agreements and that is often a way to maximize the profitability of the business. The legal nature of the act of agreement to use prices to limit competition revealed in the price fixing agreement is an agreement between enterprises on the same relevant market.